Microvascular Free-Flap Head and Neck Reconstruction: The Utility of the Modified Frailty Five-Item Index - Othman, Sammy; Robinson, Emma; Kamdar, Dev; Pereira, Lucio; Miles, Brett; Kasabian, Armen; Ricci, Joseph A.; Knobel, Denis (Journal of Reconstructive Microsurgery, 2024)
Background Microvascular free tissue transfer is a common tool for the reconstruction of oncologic head and neck defects. Adequate preoperative assessment can aid in appropriate risk stratification and peri-operative optimization. The modified five-item frailty index (mFI-5) is a validated risk-assessment scale; however, its utility in head and neck free-flap reconstruction is unknown when compared with other common risk factors.Methods A retrospective, single-institution chart review (2017–2020) was performed. Patient demographics, defect and repair characteristics, pre- and peri-operative factors, and flap outcomes were recorded. A high mFI-5 score was defined as greater than 2. The total score, as well as other patient factors, was correlated to postoperative flap complications.Results A total of 214 patients were deemed appropriate for conclusion. The mean age was 63.9 ± 12.8 years. There were an even number of males (52.8%) and females (47.2%). A fifth of subjects (20.8%) underwent preoperative radiotherapy. There were 21 cases (9.8%) of complete flap loss. A total of 34 patients (29.4%) experienced any postoperative complication related to flap outcomes. An elevated mFI-5 was significantly associated with a higher overall rate of postoperative complications (39.7 vs. 29.4%, p < 0.019) and total flap loss (16.7% vs. 6.6%, p < 0.033). Preoperative radiation was found to be associated with an increased complication rate (p < 0.003).Conclusion The mFI-5 score may be a potentially significant tool in the risk stratification of patients undergoing head and neck free-flap reconstruction as opposed to commonly utilized risk factors. Preoperative radiotherapy is significantly associated with postoperative complications. Appropriate preoperative assessment may help tailor patient care preoperatively.
Keywords: microvascular surgery; head and neck; reconstruction